The VSOP 5 GHz Active Galactic Nucleus Survey. V. Imaging Results for the Remaining 140 - Dodson, R.; Formalont, E.; Wiik, K.; Horiuchi, S.; Hirabayashi, H.; Edwards, P.; Murata, Y.; Asaki, Y.; Moellenbrock, G.; Scott, W.; Taylor, A.; Gurvits, L.; et al. (The American Astronomical Society, 2008)
In 1997 February, the Japanese radio astronomy satellite HALCA was launched to provide the space-bourne element for the VLBI Space Observatory Program (VSOP) mission. Approximately 25% of the mission time was dedicated to the VSOP survey of bright compact active galactic nuclei (AGNs) at 5 GHz. This paper, the fifth in the series, presents images and models for the remaining 140 sources not included in the third paper in the series, which contained 102 sources. For most sources, the plots of the (u,v) coverage, the visibility amplitude versus (u,v) distance, and the high-resolution image are presented. Model fit parameters to the major radio components are determined, and the brightness temperature of the core component for each source is calculated. The brightness temperature distributions for all of the sources in the VSOP AGN survey are discussed.